2017
DOI: 10.1177/0363546517701911
|View full text |Cite
|
Sign up to set email alerts
|

Management of Posterior Cruciate Ligament Tibial Avulsion Injuries: A Systematic Review

Abstract: In patients with displaced tibial-sided PCL avulsion fractures treated operatively, surgical approaches render similar outcomes and risks. While the arthroscopic group had somewhat higher subjective and objective knee outcome scores, it demonstrated a slightly higher rate of arthrofibrosis. The clear advantage of the arthroscopic approach is that concomitant intra-articular injuries seen on preoperative magnetic resonance imaging, such as meniscal tears or osteochondral loose fragments, can be addressed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 38 publications
0
110
1
1
Order By: Relevance
“… 8 , 11 , 15 Recently, suture fixation was used in arthroscopic surgery of PCL avulsion fractures, and good postoperative outcomes were reported. 5 , 17 Nonabsorbable suture fixation can have many advantages. First, suture fixation for an avulsion fracture of the tibial spine or plateau is elastic and also netlike, which is superior to rigid fixation, especially in some comminuted fracture cases 13 and in adolescents whose epiphysis is not closed.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 11 , 15 Recently, suture fixation was used in arthroscopic surgery of PCL avulsion fractures, and good postoperative outcomes were reported. 5 , 17 Nonabsorbable suture fixation can have many advantages. First, suture fixation for an avulsion fracture of the tibial spine or plateau is elastic and also netlike, which is superior to rigid fixation, especially in some comminuted fracture cases 13 and in adolescents whose epiphysis is not closed.…”
Section: Discussionmentioning
confidence: 99%
“…Tibial avulsions of PCL are due to motor vehicle accidents in 68.4% of cases and out of these 59% are due to motor cycle accidents. 23 They are more common in countries like India and China than in the western world because use of motor cycles is more in these countries. Like ACL avulsions, PCL avulsions are also more common in children than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…9 . several methods were mentioned for tibial spine avulsion fixation of like cannulated screws, suture anchors 10 , and non-absorbable pull-out sutures 11. Our study verified that there is major improvement of postoperative Lysholm score. This comes in consistence with what reported by Sinha et al, 12 who confirmed that union of avulsed tibial spine in all cases, stability success and considerable improvement in Lysholm score refer to the efficiency of our technique.…”
Section: Figmentioning
confidence: 99%